2015
DOI: 10.1371/journal.pone.0120799
|View full text |Cite|
|
Sign up to set email alerts
|

Modelling Terrestrial and Marine Foraging Habitats in Breeding Audouin's Gulls Larus audouinii: Timing Matters

Abstract: Although the breeding ecology of Audouin’s gull has been widely studied, its spatial distribution patterns have received little attention. We assessed the foraging movements of 36 GPS-tracked adult Audouin’s gulls breeding at the Ebro Delta (NW Mediterranean), coinciding with the incubation period (May 2011). This also coincided with a trawling moratorium northwards from the colony. We modelled the distribution of the gulls by combining these tracking data with environmental variables (including fishing activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 66 publications
1
33
2
Order By: Relevance
“…Nevertheless, this result agrees with previous studies carried out in the western Mediterranean, which found an increase in the probability of birds attending longliners and/or greater incidental catches during non-working days of the trawlers (García- Barcelona et al 2010, Laneri et al 2010, Báez et al 2014, Soriano-Redondo et al 2016. Trawler discards have a great influence on foraging behaviour of scavenging species (Bartumeus et al 2010, Cama et al 2013, Bécares et al 2015, so the absence of trawler activity can induce birds to search for alternative food resources, such as bait used by longline vessels.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this result agrees with previous studies carried out in the western Mediterranean, which found an increase in the probability of birds attending longliners and/or greater incidental catches during non-working days of the trawlers (García- Barcelona et al 2010, Laneri et al 2010, Báez et al 2014, Soriano-Redondo et al 2016. Trawler discards have a great influence on foraging behaviour of scavenging species (Bartumeus et al 2010, Cama et al 2013, Bécares et al 2015, so the absence of trawler activity can induce birds to search for alternative food resources, such as bait used by longline vessels.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction of discards is therefore likely to result in a substantial increase in bycatch rates of Scopoli’s shearwaters, to a level that could be completely unsustainable for some western Mediterranean populations29. Moreover, our results can reasonably be extrapolated to other seabirds species targeting trawler discards in the Mediterranean which are also known to be caught in longlines, such as the Audouin’s gull and the Yelkouan and Balearic shearwaters23. The latter is of particular concern given its sensitive conservation status, since bycatch appears to account for almost half the adult mortality estimated for the species8.…”
Section: Discussionmentioning
confidence: 76%
“…around 230,000 tonnes discarded annually), with trawlers being responsible for 15 to 65% of the discards18. Discard availability modifies the diet, foraging strategies and distribution of seabirds21222324, with some species obtaining up to 75% of their energy needs from this resource2513.…”
mentioning
confidence: 99%
“…One major goal of the Common Fisheries Policy of the European Union is a discard ban, which will be fully implemented in 2020. The degree of both immediate and long-term consequences of such policy for scavenging seabirds is still poorly understood and long-term seabird monitoring is needed, especially for gull species that show a great dependence on discards (Bicknell et al 2013, Bécares et al 2015. Although Audouin's and yellow-legged gulls breeding populations in southern Portugal are recent (first breeding attempts of Audouin's gulls in 2000; Cabral et al 2005) and currently of relatively small size (ca 1200 and 900 breeding pairs of Audouin's and yellow-legged gulls, respectively), their numbers are increasing exponentially (ca 300 breeding pairs per year; unpublished data), most likely due to the presence of intense fishing activities in the colony surroundings and abundance of fishery discards.…”
Section: On the Use Of Fisheries Subsidiesmentioning
confidence: 99%